Preparation method of mesoporous Cu-N-C zinc-air battery air cathode material
By liquid adsorbing cupric amino ions in mesoporous NC and pyrolyzing the mesoporous Cu-N-C material, the problem of easy aggregation of Cu metal in zinc-air batteries is solved, and efficient oxygen reduction reaction and excellent battery performance are achieved.
Patent Information
- Application Number
- CN202510124189.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-15
AI Technical Summary
The efficiency of oxygen reduction and redox reactions in existing zinc-air batteries is low, resulting in high overpotential of the battery, and the resources of platinum-based catalysts are scarce and costly. Cu metals are prone to aggregation during the pyrolysis process, affecting the electrocatalytic performance.
By adsorbing the liquid phase of the cupric ammonia ion [Cu(NH3)4]2+ in the mesoporous NC prepared by the hard template method, the mesoporous Cu-N-C material was obtained by high temperature pyrolysis, which effectively reduces the size of Cu metal particles and enhances its dispersion and oxygen reduction activity.
The high power density and excellent charge and discharge cycle stability of mesoporous Cu-N-C materials are achieved, and the overall performance of zinc-air batteries is improved.
Smart Images

Figure CN119833651A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a mesoporous Cu-NC zinc-air battery air cathode material, and belongs to the application field of zinc-air batteries. Background Art
[0002] Zinc-air batteries are considered to have certain application prospects in the field of energy storage due to their abundant zinc reserves, high operating efficiency, good safety and environmental friendliness. In zinc-air batteries, ORR and OER are two basic catalytic reactions that occur at the air cathode during the battery cycle, but they proceed very slowly in the natural environment, with extremely low efficiency and high overpotential of the battery. Therefore, the development of efficient, stable and economical oxygen electrocatalysts to accelerate the slow oxygen electrocatalytic process is crucial to improving the overall performance of zinc-air batteries. Platinum-based catalysts perform well in oxygen reduction reactions, but their scarce resources, high cost and poor stability hinder their large-scale application in zinc-air batteries.
[0003] Copper-based catalysts have attracted widespread attention due to their abundant reserves, low prices, and adjustable electronic structure. In the preparation process of copper-based electrocatalysts, pyrolysis is a key step, which can affect the structure and surface chemical component state of the catalyst, thereby affecting the electrocatalytic activity. However, during the pyrolysis process of copper-based electrocatalysts, Cu metal is very easy to aggregate, which will lead to a reduction in the active sites of the catalyst, thereby affecting its electrocatalytic performance. Therefore, controlling the aggregation of Cu metal in copper-based electrocatalysts and optimizing its dispersibility are the keys to improving the performance of copper-based electrocatalysts. We can improve the reduction performance of copper-based electrocatalysts by precisely controlling the size, composition, morphology, and structure of copper-based electrocatalysts. For example, by reducing the particle size of metal nanoparticles, the specific surface area of the catalyst can be increased, thereby affecting the catalytic activity and stability. Based on the above background, in order to reduce the size of Cu metal particles, this patent uses copper ammonium ions ([Cu(NH3)4] 2+ ) replaces copper ions (Cu 2+ ), adsorbed its liquid phase into the mesoporous NC prepared by the hard template method, and obtained the mesoporous Cu-NC material after high-temperature pyrolysis. This material not only effectively reduces the size of Cu metal particles, but also has rich mesoporous structure and excellent oxygen reduction activity. As the air cathode of zinc-air battery, it achieves high power density and excellent charge and discharge cycle stability, and has certain application prospects in the field of zinc-air batteries. Summary of the invention
[0004] The purpose of the present invention is to provide an air cathode material for a zinc-air battery with excellent performance. The specific steps of the preparation method are as follows: A method for preparing a mesoporous Cu-NC material comprises the following steps: Step 1: pre-pyrolyze the zinc-based imidazole framework precursor embedded with SiO2 nanoparticles under an inert atmosphere to obtain nitrogen-doped carbon NC powder containing SiO2 nanoparticles; Step 2: Soaking the nitrogen-doped carbon powder containing SiO2 nanoparticles in a hydrofluoric acid solution, stirring, removing the SiO2 nanoparticles, and then centrifuging and washing the product to obtain mesoporous NC; Step 3: Prepare a certain concentration of copper ammonium ions [Cu(NH3)4] 2+ solution, adding mesoporous NC, ultrasonicating and stirring at room temperature, centrifugal drying, and pyrolysis at high temperature to obtain mesoporous Cu-NC material.
[0005] SiO2 nanoparticles are added to a zinc nitrate alcohol solution, and then a dimethylimidazole alcohol solution is added, and the mixture is allowed to stand at 50-70°C for precipitation to obtain a ZIF-8 precursor with SiO2 nanoparticles embedded therein.
[0006] The particle size of the SiO2 nanoparticles is less than 15 nm.
[0007] SiO2 nanoparticles have excellent chemical stability. Embedding them into the zinc-based imidazole framework will not only not destroy the growth of the imidazole framework, but also occupy space within the framework. After etching the SiO2 nanoparticles with hydrofluoric acid, a large number of pores can be formed within the framework. Compared with other methods, the size of SiO2 nanoparticles is easy to control. By selecting SiO2 nanoparticles with a particle size of about 15nm, we can directly obtain a large number of mesopores in imidazole-derived NCs.
[0008] In step 1, the pyrolysis temperature is 800-1000° C. and the pyrolysis time is 1-3 h.
[0009] The mass concentration of the hydrofluoric acid solution is 30-42%.
[0010] [Cu(NH3)4] 2+ The solution is prepared by mixing copper salt and ammonia water; the copper salt includes any one of copper sulfate pentahydrate, copper chloride and copper nitrate.
[0011] The [Cu(NH3)4] 2+ The concentration of the solution is 5-15 mg / mL.
[0012] [Cu(NH3)4] 2+ The solution is a copper-ammine complex solution, where Cu²⁺ ions and ammonia molecules are bound by coordination bonds to form a stable [Cu(NH3)4] 2+Complex. This stable complex structure allows the Cu ions to be evenly dispersed in the solution, thereby forming smaller Cu particles during the reduction process. In addition, compared to individual Cu²⁺ ions, the presence of ammonia molecules can prevent the agglomeration of Cu particles, further reducing the particle size.
[0013] A mesoporous Cu-NC material is prepared by the method described, wherein the mesoporous Cu-NC material has characteristic diffraction peaks at about 25°, 43.3°, 50.4° and 74.1°.
[0014] The diffraction peak at about 25° corresponds to the (002) crystal plane of graphitized carbon. In addition, the diffraction peaks at 43.3°, 50.4° and 74.1° correspond to the (111), (200) and (220) crystal planes of Cu metal particles, respectively (PDF#85-1326), indicating that the obtained phases are Cu metal particles and graphitized carbon. Graphitized carbon has excellent electrical conductivity and can effectively promote the transmission of electrons. In addition, the synergistic effect between Cu metal particles and graphitized carbon can optimize the electron transmission path, enhance the activity and stability of the catalyst, and thus improve the overall performance of the battery.
[0015] A cathode material is a mesoporous Cu-NC material prepared by the method.
[0016] A mesoporous Cu-NC zinc-air battery comprises the cathode material.
[0017] The catalyst was evenly drop-coated on the hydrophobic HCP120 carbon paper as the air cathode, the polished zinc plate as the anode, and the PANa hydrogel film as the electrolyte to assemble the quasi-solid-state zinc-air battery. The catalyst was evenly drop-coated on the hydrophobic HCP120 carbon paper as the air cathode, the polished zinc plate as the anode, and the KOH solution containing 0.2 M Zn(OAc)2·2H2O as the electrolyte to assemble the liquid zinc-air battery.
[0018] The catalyst preparation method of the present invention has the following significant features: (1) The zinc-based imidazole framework (ZIF-8) precursor embedded with SiO2 nanoparticles (~15 nm) was evenly spread in a corundum boat, pre-pyrolyzed in a tube furnace, and then immersed in a 40% hydrofluoric acid solution to remove the SiO2 nanoparticles to obtain mesoporous nitrogen-doped carbon NC.
[0019] (2) Adsorption of copper ammonium ions [Cu(NH3)4] through liquid phase 2+Thus, a mesoporous Cu-NC material is obtained. This method not only effectively reduces the size of Cu metal particles, but also has a rich mesoporous structure and excellent oxygen reduction activity. As the air cathode of zinc-air batteries, it achieves high power density and excellent charge and discharge cycle stability, and has certain application prospects in the field of zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 TEM images of mesoporous nitrogen-doped carbon NCs.
[0021] Figure 2 TEM spectrum of the sample prepared in Example 1.
[0022] Figure 3 XRD pattern of the sample prepared in Example 1.
[0023] Figure 4 XRD pattern of the sample prepared in Example 4.
[0024] Figure 5 LSV curves of samples prepared in Examples 1, 2, 3, and 4 and Pt / C.
[0025] Figure 6 Chronoamperometric curve of oxygen reduction reaction of the sample prepared in Example 1.
[0026] Figure 7 LSV curve of the GDE test of the sample prepared in Example 1.
[0027] Figure 8 The power density curve of the quasi-solid-state battery assembled from the samples prepared in Example 1.
[0028] Fig. 9 The sample prepared in Example 1 was used as the air cathode of a quasi-solid-state battery at a current density of 2 mA cm -2 Constant current cycle charge and discharge curve.
[0029] Fig.10 The sample prepared in Example 1 was used as the air cathode of the liquid battery at a current density of 10 mA cm -2 Constant current cycle charge and discharge curve.
[0030] Fig.11 LSV curves of the samples prepared in Examples 5 and 6.
[0031] Fig.12 The sample prepared in Example 6 was used as the air cathode of a quasi-solid-state battery at a current density of 2 mA cm -2 Constant current cycle charge and discharge curve.
[0032] Fig.13TEM spectrum of the sample prepared in Example 7. DETAILED DESCRIPTION
[0033] Example 1 In the first step, 3.57 g of zinc nitrate hexahydrate and 3.94 g of dimethylimidazole were dissolved in 100 mL of methanol solution, 2 g of SiO2 nanoparticles (~15 nm) were added to the zinc nitrate solution, and then the zinc nitrate solution was added to the dimethylimidazole solution and stirred for 30 min, and then kept at 60 °C for 12 h. The precipitate was washed by centrifugation with methanol for 3 times, and dried in a vacuum drying oven for 12 h to obtain the ZIF-8 precursor with SiO2 nanoparticles embedded inside. Then it was evenly spread in a corundum boat, placed in the center of a tube furnace, heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere, kept warm for 2 h, and cooled to room temperature to obtain nitrogen-doped carbon (NC) powder containing SiO2 nanoparticles; In the second step, the NC powder containing SiO2 nanoparticles was immersed in a 40% hydrofluoric acid solution and stirred for 6 h to remove SiO2, and then the product was centrifuged and washed to obtain mesoporous nitrogen-doped carbon NC; In the third step, 10 mg of copper sulfate pentahydrate was dissolved in 10 mL of pure water, and 1 mL of ammonia water was added and stirred for 10 min to obtain a copper ammonium ion ([Cu(NH3)4] 2+ ) solution. 100 mg of mesoporous NC powder was added, ultrasonic treatment was performed at room temperature for 1 h, and stirring was performed for 2 h for liquid phase adsorption. The product was centrifuged and dried, and then heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere and kept at this temperature for 2 h, and then cooled to room temperature to obtain a mesoporous Cu-NC material, which was marked as Example 1.
[0034] First, the mesoporous NC was tested by transmission electron microscopy ( Figure 1 ), we can see that the sample maintains the morphology of ZIF-8 rhombic dodecahedron, with a size of about 1 μm. Due to the embedding and removal of SiO2 nanoparticles, there are a large number of holes inside the sample, with a rich mesoporous structure. Figure 2 This is the TEM spectrum of the sample of Example 1. As shown in the figure, the sample maintains the morphology of mesoporous NC, and no obvious agglomerated Cu metal particles are seen. Figure 3 The XRD spectrum of Example 1 prepared under this embodiment is shown in the figure. As shown in the figure, the diffraction peaks at about 26° and 43° correspond to the (002) crystal plane and (101) crystal plane of graphitized carbon. In addition, the diffraction peaks at 43.3°, 50.4° and 74.1° correspond to the (111), (200) and (220) crystal planes of Cu metal particles, respectively (PDF#85-1326), indicating that the physical phases of Example 1 are Cu metal particles and graphitized carbon.
[0035] The sample of this embodiment was prepared into a slurry, dropped onto a rotating disk electrode, and its ORR performance was tested in an O2-saturated 0.1 M KOH solution. Figure 5 The ORR LSV curve shows that at 1600 rpm, the half-wave potential of Example 1 is 0.88 V vs. RHE, and the limiting current density is 6.10 mA cm -2 , the starting potential is 0.95 V vs. RHE. Obviously, the ORR performance of Example 1 is better than that of Pt / C, showing excellent ORR performance. Figure 6 The chronoamperometric curve of the oxygen reduction reaction of the sample in Example 1. After 3 hours, the current retention rate of Example 1 is still 83%, indicating its good stability. Considering the rich mesoporous structure of the sample, we conducted a gas diffusion electrode (GDE) half-cell test on the sample in Example 1 to measure its mass transfer performance. Figure 7 As shown in the LSV curve, under the same test conditions, the maximum value of the sample in Example 1 reached nearly 600 mA cm -2 (In comparison, Pt / C is 160 mA cm -2 ), and has a smaller overpotential than Pt / C in the kinetic-diffusion controlled potential region (about 0.9-0.6 V vs. RHE), which proves that the abundant mesopores in the sample of Example 1 significantly promote mass transfer. Figure 8 The discharge and power density curves of the quasi-solid-state battery assembled in Example 1. The battery power density is calculated to be 454 mW cm -2 The battery was placed at 2 mA cm -2 Cyclic charge and discharge at a constant current density can be stably cycled for 23 h ( Fig. 9 The liquid battery assembled from the sample of this embodiment was tested at 10 mA cm -2 Cyclic charge and discharge at a constant current density can be stably cycled for more than 1300 h ( Fig.10 ) It can be concluded that Example 1 has excellent battery performance as an air cathode.
[0036] Example 2 In the first step, 3.57 g of zinc nitrate hexahydrate and 3.94 g of dimethylimidazole were dissolved in 100 mL of methanol solution, 2 g of SiO2 nanoparticles (~15 nm) were added to the zinc nitrate solution, and then the zinc nitrate solution was added to the dimethylimidazole solution and stirred for 30 min, and then kept at 60 °C for 12 h. The precipitate was washed by centrifugation with methanol for 3 times, and dried in a vacuum drying oven for 12 h to obtain the ZIF-8 precursor with SiO2 nanoparticles embedded inside. Then it was evenly spread in a corundum boat, placed in the center of a tube furnace, heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere, kept warm for 2 h, and cooled to room temperature to obtain nitrogen-doped carbon (NC) powder containing SiO2 nanoparticles; In the second step, the NC powder containing SiO2 nanoparticles was immersed in a 40% hydrofluoric acid solution and stirred for 6 h to remove SiO2, and then the product was centrifuged and washed to obtain mesoporous nitrogen-doped carbon NC; In the third step, 12 mg of copper sulfate pentahydrate was dissolved in 10 mL of pure water, and 1 mL of ammonia water was added and stirred for 10 min to obtain a copper ammonium ion ([Cu(NH3)4] 2+ ) solution. 100 mg of mesoporous NC was added, ultrasonic treatment was performed at room temperature for 1 h, and stirring was performed for 2 h for liquid phase adsorption. The product was centrifuged and dried, and then heated to 900°C at a heating rate of 5°C / min in an Ar atmosphere and kept at this temperature for 2 h, and cooled to room temperature to obtain a mesoporous Cu-NC material, which was marked as Example 2.
[0037] The sample of this example was prepared into a slurry and then ultrasonically dispersed, and then drop-coated on a rotating disk electrode. After uniform film formation, the ORR performance was tested at a rotation speed of 1600 rpm using a 0.1 M KOH solution saturated with O2 as the electrolyte. The LSV curve of the sample of this example is shown in FIG. Figure 5 As shown in Example 2, its half-wave potential is 0.87 V vs. RHE and the limiting current density is 5.76 mA cm -2 The starting potential is 0.95 V vs. RHE, and its ORR performance is excellent, almost the same as that of Example 1.
[0038] Example 3 In the first step, 3.57 g of zinc nitrate hexahydrate and 3.94 g of dimethylimidazole were dissolved in 100 mL of methanol solution, 2 g of SiO2 nanoparticles (~15 nm) were added to the zinc nitrate solution, and then the zinc nitrate solution was added to the dimethylimidazole solution and stirred for 30 min, and then kept at 60 °C for 12 h. The precipitate was washed by centrifugation with methanol for 3 times, and dried in a vacuum drying oven for 12 h to obtain the ZIF-8 precursor with SiO2 nanoparticles embedded inside. Then it was evenly spread in a corundum boat, placed in the center of a tube furnace, heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere, kept warm for 2 h, and cooled to room temperature to obtain nitrogen-doped carbon (NC) powder containing SiO2 nanoparticles; In the second step, the NC powder containing SiO2 nanoparticles was immersed in a 40% hydrofluoric acid solution and stirred for 6 h to remove SiO2, and then the product was centrifuged and washed to obtain mesoporous nitrogen-doped carbon NC; In the third step, 15 mg of copper sulfate pentahydrate was dissolved in 10 mL of pure water, and 1 mL of ammonia water was added and stirred for 10 min to obtain a copper ammonium ion ([Cu(NH3)4] 2+ ) solution. 100 mg of mesoporous NC was added, ultrasonic treatment was performed at room temperature for 1 h, and stirring was performed for 2 h for liquid phase adsorption. The product was centrifuged and dried, and then heated to 900°C at a heating rate of 5°C / min in an Ar atmosphere and kept at this temperature for 2 h. The product was cooled to room temperature to obtain a mesoporous Cu-NC material, which was marked as Example 3.
[0039] The sample of this example was prepared into a slurry and then ultrasonically dispersed, and then drop-coated on a rotating disk electrode. After uniform film formation, the ORR performance was tested at a rotation speed of 1600 rpm using a 0.1 M KOH solution saturated with O2 as the electrolyte. The LSV curve of the sample of this example is shown in FIG. Figure 5 As shown in Example 3, its half-wave potential is 0.86 V vs. RHE and the limiting current density is 5.19 mA cm -2 , with an onset potential of 0.94 V vs. RHE, and its ORR performance is close to that of Pt / C.
[0040] Example 4 In the first step, 3.57 g of zinc nitrate hexahydrate and 3.94 g of dimethylimidazole were dissolved in 100 mL of methanol solution, 2 g of SiO2 nanoparticles (~15 nm) were added to the zinc nitrate solution, and then the zinc nitrate solution was added to the dimethylimidazole solution and stirred for 30 min, and then kept at 60 °C for 12 h. The precipitate was washed by centrifugation with methanol for 3 times, and dried in a vacuum drying oven for 12 h to obtain the ZIF-8 precursor with SiO2 nanoparticles embedded inside. Then it was evenly spread in a corundum boat, placed in the center of a tube furnace, heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere, kept warm for 2 h, and cooled to room temperature to obtain nitrogen-doped carbon (NC) powder containing SiO2 nanoparticles; In the second step, the NC powder containing SiO2 nanoparticles was immersed in a 40% hydrofluoric acid solution and stirred for 6 h to remove SiO2, and then the product was centrifuged and washed to obtain mesoporous nitrogen-doped carbon NC; In the third step, 10 mg of copper chloride dihydrate was dissolved in 10 mL of pure water, and 1 mL of ammonia water was added and stirred for 10 min to obtain a copper ammonium ion ([Cu(NH3)4] 2+ ) solution. 100 mg of mesoporous NC was added, ultrasonic treatment was performed at room temperature for 1 h, and stirring was performed for 2 h for liquid phase adsorption. The product was centrifuged and dried, and then heated to 900°C at a heating rate of 5°C / min in an Ar atmosphere and kept at this temperature for 2 h, and cooled to room temperature to obtain a mesoporous Cu-NC material, which was marked as Example 4.
[0041] Figure 4 This is the XRD spectrum of sample Example 4 prepared under this embodiment. As shown in the figure, the diffraction peaks at about 26° and 43° correspond to the (002) crystal plane and (101) crystal plane of graphitized carbon. In addition, the diffraction peaks at 43.3°, 50.4° and 74.1° correspond to the (111), (200) and (220) crystal planes of Cu metal particles, respectively (PDF#85-1326), indicating that the physical phases of Example 4 are Cu metal particles and graphitized carbon. The slurry prepared from the sample of this embodiment is ultrasonically dispersed and drop-coated on a rotating disk electrode. After uniform film formation, the ORR performance is tested at a rotation speed of 1600 rpm using an O2-saturated 0.1 M KOH solution as the electrolyte. The LSV curve of the sample of this embodiment is shown in FIG. Figure 5 As shown in Example 4, its half-wave potential is 0.86 V vs. RHE and the limiting current density is 5.46 mA cm -2 The onset potential is 0.94 V vs. RHE, and the ORR performance is close to that of Pt / C, which has good ORR performance.
[0042] Compared with Example 1, the experimental steps and other drug dosages are kept unchanged, and the copper sulfate pentahydrate in Example 1 is replaced with copper acetate. The ORR LSV curve of the obtained mesoporous Cu-NC material corresponding to the sample is as follows: Fig.11 As shown in Example 5. As can be seen from the figure, at 1600 rpm, its half-wave potential drops to 0.85 V vs. RHE, and the limiting current density drops to 5.4 mA cm -2 , its ORR performance is obviously attenuated.
[0043] Compared with Example 1, the experimental steps and the dosage of other drugs remain unchanged, and the liquid phase adsorbed copper ammonium ions ([Cu(NH3)4] 2+ ) is replaced by copper sulfate (Cu 2+ ), the ORR LSV curve of the obtained sample is as follows Fig.11 As shown in Example 6, it can be seen from the figure that at 1600 rpm, its half-wave potential drops to 0.85 V vs. RHE, and the limiting current density drops to 5.5 mA cm -2 , its ORR performance is obviously attenuated. Fig.12 This cell is charged at 2 mA cm -2 The cyclic charge and discharge under constant current density can only be stably cycled for 15 h, which shows that its battery performance is poor.
[0044] Compared with Example 1, instead of using SiO2 nanoparticles (~15 nm) to form pores, the Zn species in ZIF-8 are crystallized into Zn grains (~2 nm), which are then removed by acid washing to obtain smaller mesoporous NCs of 2-4 nm. 2+ The obtained sample is labeled as Example 7, and its TEM Fig.13 As shown in Figure 2, the size of Cu particles increases to ~300-400 nm. Too large Cu metal particles are not conducive to the exposure of catalytic sites, which in turn reduces the catalytic performance and the overall performance of the battery.
Claims
1. A method for preparing a mesoporous Cu-NC material, characterized in that: The steps include: Step 1: pre-pyrolyze the zinc-based imidazole framework precursor embedded with SiO2 nanoparticles under an inert atmosphere to obtain nitrogen-doped carbon NC powder containing SiO2 nanoparticles; Step 2: Soaking the nitrogen-doped carbon powder containing SiO2 nanoparticles in a hydrofluoric acid solution, stirring, removing the SiO2 nanoparticles, and then centrifuging and washing the product to obtain mesoporous NC; Step 3: Prepare a certain concentration of copper ammonium ions [Cu(NH3)4] 2+ solution, adding mesoporous NC, ultrasonicating and stirring at room temperature, centrifugal drying, and pyrolysis at high temperature to obtain mesoporous Cu-NC material.
2. The method for preparing the mesoporous Cu-NC material according to claim 1, characterized in that: SiO2 nanoparticles are added into zinc nitrate alcohol solution, and then dimethylimidazole alcohol solution is added, and the mixture is allowed to stand at 50-70°C for precipitation to obtain a ZIF-8 precursor with SiO2 nanoparticles embedded inside.
3. The method for preparing the mesoporous Cu-NC material according to claim 2, characterized in that: The particle size of the SiO2 nanoparticles is less than 15 nm.
4. The method for preparing the mesoporous Cu-NC material according to claim 1, characterized in that: In step 1, the pyrolysis temperature is 800-1000° C. and the pyrolysis time is 1-3 h.
5. The method for preparing the mesoporous Cu-NC material according to claim 1, characterized in that: The mass concentration of the hydrofluoric acid solution is 30-42%.
6. The method for preparing the mesoporous Cu-NC material according to claim 1, characterized in that: [Cu(NH3)4] 2+ The solution is prepared by mixing copper salt and ammonia water; the copper salt includes any one of copper sulfate pentahydrate, copper chloride and copper nitrate.
7. The method for preparing the mesoporous Cu-NC zinc-air battery air cathode material according to claim 1, characterized in that: The [Cu(NH3)4] 2+ The concentration of the solution is 5-15 mg / mL.
8. A mesoporous Cu-NC material, characterized in that: The mesoporous Cu-NC material is prepared by the method described in any one of claims 1 to 7, and has characteristic diffraction peaks at about 25°, 43.3°, 50.4° and 74.1°.
9. A cathode material, characterized in that: The mesoporous Cu-NC material is prepared by the method described in any one of claims 1 to 7.
10. Mesoporous Cu-NC zinc-air battery, characterized in that: Comprising the cathode material according to claim 9.
Citation Information
Cited By
Cathode catalyst for air battery and preparation method of cathode catalyst
CN121460608A